Perception and Attitude of MBBS, Dental & Nursing Students and Paramedical Staff Towards COVID Vaccination and Pandemic Preparedness: A Cross-Sectional Study in Four Tertiary Level Hospitals and a Nursing College in India - Behal, Varun; Chelani, Palak; Garg, Radhika; Kumar, Udit; Azeem, Abdul; Maurya, Siddhi; Garg, Hemant Kumar; Singh, Rukmini (Journal of Neonatal Surgery, 2025)
Background:The COVID-19 pandemic emphasized the necessity of vaccination, infection control, and pandemic preparedness among healthcare professionals and students. Understanding their perceptions and attitudes is vital for shaping future health policies and preparedness strategies. Objectives:To assess the perception and attitude toward COVID-19 vaccination and pandemic preparedness among MBBS students and interns, nursing students, BDS students, and technical & nursing staff in tertiary care settings in India. Methods:A descriptive cross-sectional study was conducted among 350 participants — 100 MBBS students and interns, 100 nursing students, 50 BDS students, and 100 technical & nursing staff — from four tertiary-level hospitals and one nursing college in India. A 15-item, 5-point Likert scale questionnaire assessed participants’ perceptions and attitudes regarding COVID-19 vaccination and pandemic preparedness. Data were analyzed using descriptive statistics, Chi-square tests, and Pearson correlation. Results:Overall, 89.4% participants reported being vaccinated with at least two doses. A high positive attitude toward vaccination was observed (mean Likert score = 4.31 ± 0.56). MBBS students demonstrated the highest awareness scores (mean = 4.47 ± 0.48), followed by BDS (4.33 ± 0.52), nursing students (4.21 ± 0.61), and technical/nursing staff (4.05 ± 0.66). Knowledge and attitude were significantly correlated (r = 0.72, p < 0.01). Pandemic preparedness perception was strongest among MBBS students (86%) and weakest among technical staff (62%). Conclusion:MBBS students exhibited better understanding and preparedness toward COVID-19 vaccination and pandemic control than other groups. Continuous education, simulation-based training, and institutional awareness programs should be reinforced to improve preparedness among all healthcare cadres.